2020
DOI: 10.1080/02770903.2020.1853155
|View full text |Cite
|
Sign up to set email alerts
|

Higher inflammation and cerebral white matter injury associated with cognitive deficit in asthmatic patients with depression

Abstract: Background Depression is a common co-morbidity in asthma, worsening asthma control and impairing patient's quality of life. Previous studies have reported a higher risk of cognitive de cit in depression. However, few research has focused on the cognitive status of asthmatic patients with depression. Evidence showed that in ammation may play an important role in both asthma and depression. Moreover, cerebral white matter injury, which could be induced by in ammation, has been associated with depression. The pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Besides, HMGB1 could promote the action of other DAMPs as an internal cellular stress, thus further increasing in ammation and neuroin ammation (25). Previous studies reported that the expression of HMGB1 and TLR4 were both upregulated in the brains of patients with depression (21) and in stress-induced rats(68). In this study, the expression of HMGB1 and TLR4 were elevated under CUMS in rats' amygdalae and spleens with downregulating effects of acupuncture.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides, HMGB1 could promote the action of other DAMPs as an internal cellular stress, thus further increasing in ammation and neuroin ammation (25). Previous studies reported that the expression of HMGB1 and TLR4 were both upregulated in the brains of patients with depression (21) and in stress-induced rats(68). In this study, the expression of HMGB1 and TLR4 were elevated under CUMS in rats' amygdalae and spleens with downregulating effects of acupuncture.…”
Section: Discussionmentioning
confidence: 97%
“…High-mobility group box 1 (HMGB1) is critical in inducing and promoting the occurrence of in ammation and neuroin ammation (19,20). Studies indicate that HMGB1 can be up-regulated when stressed, accompanied with the increasing expression of its receptor in toll-like receptor 4 (TLR4) (21,22). TLR4 is an immune regulator of neuroimmune and neuroendocrine interactions in stress and depression (23).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that blood levels of HMGB1 are higher in depressed patients with asthma, 19 and that patients with high blood levels of HMGB1 during acute cerebral infarction are more likely to experience a depressive state 3 months later 20 . In addition, the HMGB1‐RAGE pathway is known to be involved in various inflammatory diseases (diabetes, rheumatoid arthritis, inflammatory kidney disease, heart disease, tumor growth, chronic obstructive pulmonary disease) 21–25 .…”
Section: Discussionmentioning
confidence: 99%
“…Досліджено чіткий зв'язок між ураженням білої речовини головного мозку за даними МРТ та когнітивними порушеннями у хворих на бронхіальну астму [26]. Дослідження свідчать про позитивний кореляційний зв'язок між пошкодженням білої речовини, визначеним за допомогою сироваткового мієлінового основного білка і мієлінового олігодендроцитарного глікопротеїну та рівнем цитокінів (ІЛ-1, ФНП-α, HMGB1-білок, Нетрин-1) у пацієнтів з бронхіальною астмою, що свідчить про вплив системного запалення на структурні зміни мозку в таких хворих [27].…”
unclassified